Offensive and defensive jihad according to Sayyid Qutb - Amir Husin bin Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2001)
This article discusses the concept of offensive and defensive jihaat according to Sayyid Qutb, one of the outstanding writers on Islamic thought of the twentieth century. Although this issue has been discussed by the traditional Muslim scholars it still attracts the present Muslim scholars to discuss it. Therefore, both the traditional and present Muslim scholars, ideas will be discussed in the earlier part of these article in order to ascertain the similarities and differences of their thoughts with those of Sayyid Qutb. Obviously, the main discussion will be focussed on Sayyid Qutb’s view on the issue